Nucleobases Undergo Dynamic Rearrangements during RNA Tertiary Folding. Issue 22 (6th November 2016) - Welty, Robb; Hall, Kathleen B.
Abstract: The tertiary structure of the GTPase center (GAC) of 23S ribosomal RNA (rRNA) as seen in cocrystals is extremely compact. It is stabilized by long-range hydrogen bonds and nucleobase stacking and by a triloop that forms within its three-way junction. Its folding pathway from secondary structure to tertiary structure has not been previously observed, but it was shown to require Mg 2 + ions in equilibrium experiments. The fluorescent nucleotide 2-aminopurine was substituted at selected sites within the 60-nt GAC. Fluorescence intensity changes upon addition of MgCl2 were monitored over a time-course from 1 ms to 100 s as the RNA folds. The folding pathway is revealed here to be hierarchical through several intermediates. Observation of the nucleobases during folding provides a new perspective on the process and the pathway, revealing the dynamics of nucleobase conformational exchange during the folding transitions. Graphical Abstract: Highlights: Mg 2 + -dependent RNA folding pathways reveal how tertiary structures utilize ions. GAC tertiary folding pathway has four intermediates; two require Mg 2 + . GAC folding kinetics range from milliseconds (local) to seconds (global). Fluorescent bases reveal transient conformational changes before global folding.